Mechanism of adhesion of glass monomeric cements of Meron and Total-cem to dentin - Nebogatov, S. S.; Chulak, L. D. (Journal of Education, Health and Sport, 2017)
Recently, researchers note an increase in the prevalence of non-carious lesions of solid dental tissues. The forms of non-carious lesions of teeth are described: erosion and abrasion, wedge-shaped defects and erosion, which were previously practically not met.Increasing the life expectancy and maintaining natural teeth also led to the fact that clinicians often began to meet with patients with increased erosion of teeth.Study of the mechanism of adherence of glass-like cements to dentin is very important. In our case, the adhesion of our cements to dentin and enamelabs of acid protrusion, in our opinion, is provided by two mechanisms. The first of these is based on the fact that carboxylate groups of the macromolecules of polyacrylic acid are capable of forming chelating compounds with calcium, in particular calcium hydroxyapatite dentin and enamel.The second possible mechanism of communication is based on the affinity of polycarboxylic acids to nitrogen of protein molecules, in particular, collagen, which is manifested by the absorption of polyacrylic acid on collagen dentin.